Can ammonia tolerance amongst lichen functional groups be explained by physiological responses? - Munzi, S; Cruz, C; Branquinho, C; Pinho, P; Leith, I D; Sheppard, L J (Environmental pollution (Barking, Essex : 1987), 2014)
Ammonia (NH3) empirical critical levels for Europe were re-evaluated in 2009, based mainly on the ecological responses of lichen communities without acknowledging the physiological differences between oligotrophic and nitrophytic species. Here, we compare a nitrogen sensitive lichen (Evernia prunastri) with a nitrogen tolerant one (Xanthoria parietina), focussing on their physiological response (Fv/Fm) to short-term NH3 exposure and their frequency of occurrence along an NH3 field gradient. Both frequency and Fv/Fm of E. prunastri decreased abruptly above 3 μg m(-3) NH3 suggesting direct adverse effects of NH3 on its photosynthetic performance. By contrast, X. parietina increased its frequency with NH3, despite showing decreased capacity of photosystem II above 50 μg m(-3) NH3, suggesting that the ecological success of X. parietina at ammonia-rich sites might be related to indirect effects of increased nitrogen (NH3) availability. These results highlight the need to establish NH3 critical levels based on oligotrophic lichen species.
Keywords: Critical levels; Environmental protection policy; Evernia prunastri; nitrogen; Xanthoria parietina

Tools for determining critical levels of atmospheric ammonia under the influence of multiple disturbances - Pinho, P; Llop, E; Ribeiro, M C; Cruz, C; Soares, A; Pereira, M J; Branquinho, C (Environmental Pollution, 2014)
Critical levels (CLEs) of atmospheric ammonia based on biodiversity changes have been mostly calculated using small-scale single-source approaches, to avoid interference by other factors, which also influence biodiversity. Thus, it is questionable whether these CLEs are valid at larger spatial scales, in a multi- disturbances context. To test so, we sampled lichen diversity and ammonia at 80 sites across a region with a complex land-cover including industrial and urban areas. At a regional scale, confounding factors such as industrial pollutants prevailed, masking the CLEs. We propose and use a new tool to calculate CLEs by stratifying ammonia concentrations into classes, and focusing on the highest diversity values. Based on the significant correlations between ammonia and biodiversity, we found the CLE of ammonia for Mediterranean evergreen woodlands to be 0.69 mgm?3, below the previously accepted value of 1.9 mgm?3, and below the currently accepted pan-European CLE of 1.0 mgm?3
Keywords: Air Pollutants; Air Pollutants: analysis; ammonia; Ammonia: analysis; Atmosphere; Atmosphere: chemistry; Biodiversity; Critical thresholds; Environmental Monitoring; Environmental Monitoring: methods; Eutrophication; Functional groups; Global change; lichens; Lichens: chemistry; Lichens: classification; nitrogen